Correction: The Interaction of the Atm Genotype with Inflammation and Oxidative Stress. - Yan Yang; Chin Wai Hui; Jiali Li; Karl Herrup (PLoS ONE, 2015)
[This corrects the article DOI: 10.1371/journal.pone.0085863.].